Development of Self-massage and Exercise Therapy in Knee Injuries - Riyadi, Slamet; Wahyudi, Agung; Rustiadi, Tri (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The purpose of this study is to produce a design product of self-massage and exercise therapy for handling knee injuries independently to help recover quickly and accurately so that they can return to sports activities comfortably. The research method used is Research and Development (R & D). The trial subjects for product testing are Persik Kendal, soccer players. The steps of the study include objective analysis, literature review, analysis of research subject characteristics, product design development, initial product preparation, expert validation, product revision, small-scale trials, revisions, large-scale trials, final product improvements. Qualitative data analysis, assessed from the feasibility of the product. The results of this study are tutorial videos and self-massage, and exercise therapy manual for knee injuries. Both products are rated right by experts with an average of 90% and 70%. The product is also considered good by media experts on the video tutorial content. The results of the application of the product on the research subjects that the study subjects experienced a decrease in pain in knee injuries after performing self-massage, and exercise therapy through video media, and guidebooks. Research conclusions in the form of manual book products, and self-massage tutorial videos, and exercise therapy to deal with knee injuries effectively applied by sports people.